2016
DOI: 10.4103/0972-2327.168635
|View full text |Cite
|
Sign up to set email alerts
|

Spinal muscular atrophy with respiratory distress syndrome (SMARD1): Case report and review of literature

Abstract: Spinal muscular atrophy with respiratory distress syndrome (SMARD1) is a rare cause of early infantile respiratory failure and death. No cases have been currently described from India. Two low-birth-weight infants presented prior to 6 months of age with recurrent apnea and respiratory distress. Both required prolonged ventilation, and had distal arthrogryposis and diaphragmatic eventration. Nerve conduction study revealed motor sensory axonopathy. Genetic testing confirmed mutations in immunoglobulin mu bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…Among the 52 literature articles screened (Supplementary Table S1) (Robison et al, 1998;Grohmann et al, 2001Grohmann et al, , 2003Guenther et al, 2004Guenther et al, , 2007Maystadt et al, 2004;Giannini et al, 2006;Wong et al, 2006;Joseph et al, 2009;AlSaman and Tomoum, 2010;Baughn et al, 2011;Pierson et al, 2011;Chalancon et al, 2012;Eckart et al, 2012;Majid et al, 2012;Messina et al, 2012;Gitiaux et al, 2013;Blaschek et al, 2014;Cottenie et al, 2014;Jedrzejowska et al, 2014;Lin et al, 2014;Litvinenko et al, 2014;Hamilton et al, 2015;Han et al, 2015;Wagner et al, 2015;Lingappa et al, 2016;Luan et al, 2016;Pedurupillay et al, 2016;San et al, 2016;Dohrn et al, 2017;Liu et al, 2017;Yuan et al, 2017;Zhang et al, 2017;Habibi et al, 2018;Kulshrestha et al, 2018;Tomaselli et al, 2018;Wu et al, 2018;Cassini et al, 2019;Kim et al, 2019;Yasui et al, 2019;Cortese et al, 2020;…”
Section: Resultsmentioning
confidence: 99%
“…Among the 52 literature articles screened (Supplementary Table S1) (Robison et al, 1998;Grohmann et al, 2001Grohmann et al, , 2003Guenther et al, 2004Guenther et al, , 2007Maystadt et al, 2004;Giannini et al, 2006;Wong et al, 2006;Joseph et al, 2009;AlSaman and Tomoum, 2010;Baughn et al, 2011;Pierson et al, 2011;Chalancon et al, 2012;Eckart et al, 2012;Majid et al, 2012;Messina et al, 2012;Gitiaux et al, 2013;Blaschek et al, 2014;Cottenie et al, 2014;Jedrzejowska et al, 2014;Lin et al, 2014;Litvinenko et al, 2014;Hamilton et al, 2015;Han et al, 2015;Wagner et al, 2015;Lingappa et al, 2016;Luan et al, 2016;Pedurupillay et al, 2016;San et al, 2016;Dohrn et al, 2017;Liu et al, 2017;Yuan et al, 2017;Zhang et al, 2017;Habibi et al, 2018;Kulshrestha et al, 2018;Tomaselli et al, 2018;Wu et al, 2018;Cassini et al, 2019;Kim et al, 2019;Yasui et al, 2019;Cortese et al, 2020;…”
Section: Resultsmentioning
confidence: 99%
“…9 Lokesh et al had reported a case of a three month old female child with SMA type 1 presented with recurrent respiratory infection in the same manner as like our study case . 10 Marie et al had reported on 80 infants with severe SMA-1, followed in France between 2012 and 2016. 7 Along with generalized weakness patients may develop chronic respiratory failure and bulbar dysfunction in infants leads to death before 2 years of age without ventilator support.…”
Section: Case Reportmentioning
confidence: 99%